Determinants of Intra-Day Stock Price Change and Asymmetric Information - Ting, Christopher Hian Ann (Institutional Knowledge at Singapore Management University, 2005)
This paper presents a synthesized model of asymmetric information. An empirical analysis of more than 1,400 NYSE common stocks shows that trade direction is more important than volume in revealing the asymmetry. There is also evidence to suggest that signed duration reflects informed trading activity. We use the proposed measure of information asymmetry to study daily changes in the level of informed trading and find that earnings announcements narrow the information gap between the informed and the uninformed. On average, information asymmetry is largest at the beginning of the trading day and it decreases monotonically toward the closing bell. More importantly, the asymmetric information measure is negatively related to the number of shareholders, number of analysts following a firm and whether there is an exchange-traded equity option written on the firm’s stock. An implication of this finding is that firms can reduce information asymmetry by implementing disclosure measures that attract not only more investors and analysts but also option writers.